The cost of the 9th item is $3.94
Since the mean cost for the 9 items in his bag was $2.71. Then, the total cost will be: = 9 × $2.71 = $24.39
In order to get the price of the 9th item, we have to calculate the price of all the 8 items given which will be:
$2.01 + $2.20 + $2.68 + $3.59 + $3.12 + $1.64, + $1.75 + $3.46 = $20.45
Therefore, the cost of the 9th item will be:
= $24.39 - $20.45
= $3.94
Read related link on:
brainly.com/question/24562826
We notice a factor of 2x in both
2x(5x^2+4x-3)
trial and error
(5x-3)(x+1) yeilds 5x^2+2x-3, nope
(5x+3)(x-1) yeilds 5x^2-2x-3, nope
(5x-1)(x+3) yeilds 5x^2+14x-3, nope
(5x+1)(x-3) yeilds 5x^2-14x-3, nope
simplest form is
2x(5x^2+4x-3)